2017
DOI: 10.3390/mi8070200
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Piezoelectric MEMS Resonators for Grape Must Fermentation Monitoring

Abstract: In this study grape must fermentation is monitored using a self-actuating/self-sensing piezoelectric micro-electromechanical system (MEMS) resonator. The sensor element is excited in an advanced roof tile-shaped vibration mode, which ensures high Q-factors in liquids (i.e., Q ~100 in isopropanol), precise resonance frequency analysis, and a fast measurement procedure. Two sets of artificial model solutions are prepared, representing an ordinary and a stuck/sluggish wine fermentation process. The precision and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…For this application, the sensor in the package is fully coated by a 4 µm thick amorphous silicon dioxide film to eliminate any parasitic leakage currents through the grape must, which would result in a lower R p value. The sensor is operated in the 15-mode and tested in model solutions N 1−9 and S 1−9 , which represent both normal and stuck fermentation stages [22]. The resonance frequency and quality factor are measured and used to calculate the density of the liquid according to [22,23].…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this application, the sensor in the package is fully coated by a 4 µm thick amorphous silicon dioxide film to eliminate any parasitic leakage currents through the grape must, which would result in a lower R p value. The sensor is operated in the 15-mode and tested in model solutions N 1−9 and S 1−9 , which represent both normal and stuck fermentation stages [22]. The resonance frequency and quality factor are measured and used to calculate the density of the liquid according to [22,23].…”
Section: Applicationsmentioning
confidence: 99%
“…The sensor is operated in the 15-mode and tested in model solutions N 1−9 and S 1−9 , which represent both normal and stuck fermentation stages [22]. The resonance frequency and quality factor are measured and used to calculate the density of the liquid according to [22,23]. Figure 8 shows both the ethanol concentration and the resonance frequency for normal as well as stuck fermentation.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-electro-mechanical system (MEMS) based sensors and actuators are used in a wide variety of applications like military, aerospace, industrial, consumer electronics, healthcare, as well as in agriculture and environment monitoring [1][2][3][4][5][6][7][8][9][10]. The devices like pressure sensors, accelerometers, gyroscope, and temperature sensors are the few most sort after MEMS sensors for these applications [8,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“… Piezoelectric MEMS resonators for measuring physical quantities such as mass, acceleration, yaw rate, as well as the pressure, viscosity, or density of liquids. Pfusterschmied et al [ 9 ] demonstrated that piezoelectric MEMS resonators with high quality factors in liquids can be used to monitor the change in grape must during wine fermentation, which is a direct quality indicator of the fermentation process. Yu et al [ 10 ] presented a unique take on the MEMS gyroscope through use of the acoustic Sagnac effect, which measured the phase difference between two sound waves traveling in opposite directions in a circular MEMS structure actuated by PMUTs.…”
mentioning
confidence: 99%